Mapping Student Information Literacy Activity against Bloom’s Taxonomy of Cognitive Skills - Judith Keene; John Colvin; Justine Sissons (Journal of Information Literacy, 2010)
This paper introduces a model of information literacy which maps the activities that students undertake against Bloom’s taxonomy of cognitive skills. Firstly, the paper summarises the authors’ underpinning research in this area. Secondly the paper proposes a model of information literacy and compares this with existing models of information literacy. Thirdly, each stage in the proposed model is articulated in more detail and the required cognitive skills for each stage are identified. Finally, the paper examines the implications of the model on how, and by whom, information literacy is delivered and supported in an academic context.
Keywords: Bloom’s taxonomy; cognition; Information literacy model